2020
DOI: 10.3389/fphar.2020.00633
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach Based on Metabolomics Coupled With Intestinal Flora Analysis and Network Pharmacology to Explain the Mechanisms of Action of Bekhogainsam Decoction in the Improvement of Symptoms of Streptozotocin-Induced Diabetic Nephropathy in Mice

Abstract: Bekhogainsam decoction (BHID), a representative prescription for the treatment of diabetes mellitus (DM) and diabetic complications in both traditional Korean and Chinese medicine, was examined for its ability to ameliorate diabetic nephropathy (DN), and its mechanism of action was evaluated by metabolomics, gut microbiota, and network pharmacology. In this study, male specific pathogen-free C57BL/6 mice were intraperitoneally injected with streptozotocin (STZ, 100 mg/kg) once per day for 3 days consecutively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…After 1 week of acclimation, followed by fasting for 12 h, DN mouse models were induced by single intraperitoneal injection of 100 mg/kg STZ, [29][30][31][32] while the normal control mice were injected with the same amount of citrate buffer. Blood samples were obtained from the tails of the mice, and fasting blood glucose (FBG) levels were measured with a glucometer (Sinocare Inc., Hunan, China).…”
Section: Modelling and Administrationmentioning
confidence: 99%
“…After 1 week of acclimation, followed by fasting for 12 h, DN mouse models were induced by single intraperitoneal injection of 100 mg/kg STZ, [29][30][31][32] while the normal control mice were injected with the same amount of citrate buffer. Blood samples were obtained from the tails of the mice, and fasting blood glucose (FBG) levels were measured with a glucometer (Sinocare Inc., Hunan, China).…”
Section: Modelling and Administrationmentioning
confidence: 99%
“…Therefore, the dysbiosis of gut microbiota has a critical effect on DKD. Increased evidence has demonstrated that a number of natural products could improve the dysbiosis of gut microbiota in DKD [68][69][70][71][72].…”
Section: Iga Nephropathymentioning
confidence: 99%
“…In a recent study, Meng and colleagues proved that Bekhogainsam decoction (BHID) affected the intestinal flora of DN mice, acting through phosphatidylinositol-3-kinase/protein kinase B and other protein targets related to MAPK. It also prevented kidney dysfunction, making it a great support in the clinical treatment of diabetic patients [162]. Jowiseungki decoction (JSD) is another possible option for ameliorating DN symptoms.…”
Section: Main Focus Salient Findings Country Year and Reference Physi...mentioning
confidence: 99%